Pengaruh Pembiayaan Bank Islam, FDI dan Pertumbuhan Ekonomi: Studi Empiris Negara OKI - Annisa Masruri Zaimsyah; Sri Herianingrum (Jurnal Ilmiah Ekonomi Islam, 2019)
The purpose of this study is studying influence between financing of Islamic Banks, FDI and Economic Growth. The methodology used is a quantitative method usning panel data. We have chosen 10 counties from Organization Islamic Conference (OIC) over the period 2009-2017. The research is the fist study to influence financing of Islamic Bank, FDI and Economic Growth in OIC Countries. The result show that the financing of Islamic Banks and FDI simultaneously and positively has a significant effect on economic growth in the OIC Countries with a significant level of 0.0000